Fundamentals of power system economics - Kirschen, Daniel S.; Strbac, Goran (Wiley, 2019)
"Fundamentals of Power System Economics, Second Edition looks at the fundamental concepts of microeconomics, organization, and operation of electricity markets, market participants' strategies, operational reliability and ancillary services, network congestion and related LMP and transmission rights, transmission investment, and generation investment. It also expands the chapter on generation investments discussing capacity mechanisms in more detail and the need for capacity markets aimed at ensuring that enough generation capacity is available when renewable energy sources are not producing due to lack of wind or sun"--Provided by publisher.